2019
DOI: 10.1634/theoncologist.2017-0664
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot, Phase II, Randomized, Open-Label Clinical Trial Comparing the Neurotoxicity of Three Dose Regimens of Nab-Paclitaxel to That of Solvent-Based Paclitaxel as the First-Line Treatment for Patients with Human Epidermal Growth Factor Receptor Type 2-Negative Metastatic Breast Cancer

Abstract: Background This study aimed to characterize the neurotoxicity of three different regimens of nab‐paclitaxel compared with a standard regimen of solvent‐based (sb) paclitaxel for the first‐line treatment of HER2‐negative metastatic breast cancer based on the Total Neurotoxicity Score (TNS), a tool specifically developed to assess chemotherapy‐induced neurotoxicity. Materials and Methods This was a randomized, open‐label study testing 4‐week cycles of 80 mg/m2 sb‐paclitaxel (PACL80/w) on days 1, 8, and 15; 100 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 17 publications
4
41
0
Order By: Relevance
“…Furthermore, in the xed weekly or triweekly nab-paclitaxel monotherapy, the incidence of grade 3/4 peripheral sensory neuropathy increased if nab-paclitaxel dosage increased. This was in accordance with the results of Ciruelos E as they found the grade 3 peripheral neuropathy was deemed to be taxanes-related, which is known to be cumulative [35].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, in the xed weekly or triweekly nab-paclitaxel monotherapy, the incidence of grade 3/4 peripheral sensory neuropathy increased if nab-paclitaxel dosage increased. This was in accordance with the results of Ciruelos E as they found the grade 3 peripheral neuropathy was deemed to be taxanes-related, which is known to be cumulative [35].…”
Section: Discussionsupporting
confidence: 91%
“…We ultimately identi ed 22 independent studies published between March 2005 and March 2020 [9,10,12,13,16,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37]. A ow chart representing selection of studies is shown in Figure 1.…”
Section: Identi Cation and Characteristics Of Studiesmentioning
confidence: 99%
“…In addition to age, a number of other potential risk factors for CIPN development have been identified. These include the cumulative dose of a chemotherapeutic agent, genetic factors, a history of neuropathy before the start of chemotherapy (e.g., painful diabetic neuropathy or neuropathy due to viral infections), impaired renal function with reduced creatinine clearance, and smoking history [9,15,17,[28][29][30][31][32].…”
Section: Prevalence Of Cipn and Risk Factorsmentioning
confidence: 99%
“…We ultimately identified 22 independent studies published between March 2005 and March 2020 [9,10,12,13,16,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37]. A flow chart representing selection of studies is shown in Figure 1 Table 1.…”
Section: Identification and Characteristics Of Studiesmentioning
confidence: 99%
“…the results of Ciruelos E as they found the grade 3 peripheral neuropathy was deemed to be taxanes-related, which is known to be cumulative[35].Concerning to the efficacy outcomes, our analysis showed nab-paclitaxel monotherapy could provide a 40% ORR, a 60% CBR, a median PFS of 7.64 months and a median OS of 24.51 months for the overall population of patients with MBC who received various doses, schedules, and regimens of nab-paclitaxel across all lines of therapy. Still, in MBC patients who received nab-paclitaxel monotherapy in the first line treatment, the nab-paclitaxel efficacy outcomes could be more encouraging with a 48.2% ORR, a 68.7% CBR, a median PFS of 8.01 months and a median OS of 24.41 months.…”
mentioning
confidence: 99%